Access to medicines in Brazil based on monetary and non-monetary acquisition data obtained from the 2008/2009 Household Budget Survey - Fernanda Caroline Silva Goes; Mauricio Homem-; Eloisa Dutra Caldas
ABSTRACT OBJECTIVE To investigate the access to medicines by Brazilian families by monetary and non-monetary acquisition data. METHODS This is a cross-sectional study based on data obtained from the 2008/2009 Brazilian Household Budget Survey. The units of assessment were households that participated in the survey and the data on the acquisition of medicines over the 30 days prior to the interviews. The medicines were classified according to the Anatomical Therapeutic Chemical classification system. RESULTS Acquisition of medicines was reported by 82.9% of Brazilian households, with 2.38 medicines/household, and 0.72 medicine/individual. In the South and Southeast regions, the average acquisition was slightly greater than the national average (2.53 and 2.49, respectively). In 22.3% of Brazilian households, it was reported that a medicine was not acquired due to lack of financial resources, mainly in the North and Northeastern regions, and in rural areas. Approximately 15.0% of medicines were obtained with no costs, 90.1% of them by the Brazilian Unified Health System. The medicines most acquired were those acting on the nervous system (28.8% of Brazilian households), on the cardiovascular system (15.7%), on the digestive tract and metabolism (14.3%), and on the respiratory system (12.1%). Overall, the quantity of medicines acquired was greater in higher socioeconomic classes of the population, with the exception of antiparasitic products, most likely because of the precarious sanitary conditions faced by less privileged social classes. CONCLUSIONS The acquisition of medicines is a common practice in Brazil, being reported by over 80.0% of the Brazilian households in 2008/2009. Although the data obtained from the Brazilian Household Budget Survey have some limitations, the information obtained in this study can help health authorities to design national and regional policies to guarantee access to these products while promoting their rational use.